2017
DOI: 10.1051/bioconf/20170901011
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of climate change indices in relation to wine production: A case study in the Douro region (Portugal)

Abstract: Climate change is of major relevance to wine production as most of the wine-growing regions of the world, in particular the Douro region, are located within relatively narrow latitudinal bands with average growing season temperatures limited to 13-21 • C. This study focuses on the incidence of climate variables and indices that are relevant both for climate change detection and for grape production with particular emphasis on extreme events (e.g. cold waves, storms, heat waves). Dynamical downscaling of MPI-ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Here, we focus on ta_o to maintain a consistent timespan with gsr. So far, there have been few studies using the mean growing season temperature for Europe and, like gsr, they are linked to viticulture in France (Neethling et al, 2012), England (Nesbitt et al, 2016) and Portugal (Blanco-Ward et al, 2017).…”
Section: Growing Season Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we focus on ta_o to maintain a consistent timespan with gsr. So far, there have been few studies using the mean growing season temperature for Europe and, like gsr, they are linked to viticulture in France (Neethling et al, 2012), England (Nesbitt et al, 2016) and Portugal (Blanco-Ward et al, 2017).…”
Section: Growing Season Indicesmentioning
confidence: 99%
“…For example, Ylhäisi et al (2010) and Irannezhad and Kløve (2015) looked at growing season parameters across Finland, Tomcyzk et al (2019) and Tomczyk and Szyga-Pluta (2019) focused on Poland and Popotova et al (2015) examined a specific region of the Czech Republic which produces a large amount of farmed vegetables. There have also been several studies applying growing season precipitation and mean growing season temperature to viticulture (wine production) in parts of Europe: the Iberian Peninsula (Blanco-Ward et al, 2007;Ramos et al, 2008;Santos et al, 2012;Moral et al, 2015;Blanco-Ward et al, 2017;Blanco-Ward et al, 2019), France (Neethling et al, 2012), England (Nesbitt et al, 2016) and Hungary (Kovacs et al, 2017). Only Santos et al (2012), Irannezhad and Kløve (2015) and Tomcyzk et al (2019) have linked the growing season indices to teleconnection patterns, although Cornes et al (2019) The aim of this study is to assess the role of four teleconnection patterns relevant to European climate in the interannual variability of three growing season indices and their contribution to trends in the indices since 1950 compared to the residual climate change trend.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above five climate-viticulture indices, the heat waves and the cold waves (the number of days below 15°C during the flowering period (NDb15), and the number of days over 35°C during the ripening period (NDh35)) have been computed and estimated based on the daily minimum temperature of May for cold waves, and the daily maximum temperature of July and August for heat waves, using cubic equations and nonlinear regressions to estimate these climatic parameters for the study area, as shown in Table 2. The frequency of heat waves during the ripening stage has a negative effect on vineyard vegetation and grapes, and on wine production, particularly when the temperature is above 35 °C (Mesterházy et al 2013;Alsafadi 2016;Blanco-ward, et al 2017). In addition, the frequency of cold waves during the flowering stage has a direct effect (Alsafadi, 2016); when the mean daily temperature was 15°C or below, no inflorescences were produced (Vasconcelos 2009).…”
Section: Fig 2 Relationship and Thresholds Between Climate And Wine Production And Quality Metrics (Jones 2015)mentioning
confidence: 99%
“…As an example, cooler climates, with a mean pre-harvest temperature below 15°C have a significant impact on -and are a clear challenge for -wine grape growth and its maturity on appropriate dates; this climate condition produces grapes and wines with lower sugar, higher acid, high pH, and lower yields per land unit (Jackson 2000). Hotter climates with a mean temperature high than 35°C during grape growth also have a negative impact (Blanco-ward, et al 2017). Due to the importance of temperature, a wide range of climate-viticulture indices have been proposed which use the temperature element as the most relevant variable for growing grapes and one essential for determining vineyard site suitability (Winkler et al 1974;Huglin 1978;Gladstones 1992;Barans et al 1946;Tonietto and Carbonneau 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation